The toppling of Ben Ali: Isolated development or first domino? Comparable challenges - varying conditions - Muriel Asseburg; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2011)
Following the fall of Tunisia's President and in light of the upheaval in Egypt, the spectre of domino effects has been raised. The lack of prospects for young people, social injustice and political repression - all causes that sparked the protests in Tunisia - are problems in virtually all Arab states. Demonstrations against the regimes have gathered force from Algiers all the way to Sana'a. Nevertheless, the Tunisian scenario is unlikely to repeat itself: the differences in political, social and economic conditions are too large. A lot depends on whether Tunisia achieves a successful transformation and on how the situation in Egypt develops. However, the developments thus far have shown that stability can be deceptive and dictators are unable to guarantee long-term stability. The EU should reconsider its benevolent policies vis-à-vis the authoritarian rulers in the Mediterranean region
Keywords: 320